A computer-assisted learning tool designed to improve clinical problem-solving skills. - Papa, F J; Meyer, S (Annals of Emergency Medicine, 1989)
A computer-based teaching and learning program was developed to supplement the case load of students on a one-month emergency medicine clinical rotation and interactively measure and support improvements in their acute chest pain differential diagnostic skills. Students using the program demonstrated a significantly higher level of diagnostic accuracy than a control group (one-tailed t test; N = 88; P less than .018). The success of the program was attributed in part to its unique application of advanced interactive software. Specifically, students use the software (an expert system shell) to develop a computer-based acute chest pain differential diagnostic protocol. Students can subsequently challenge their protocol with a number and variety of training cases in the program's data bank. The software interactively apprises students of the performance of their protocol in terms of its diagnostic accuracy against the cases. Students make protocol modifications to improve its diagnostic accuracy against the training cases. Interactive reassessments of the protocol's performance against the cases follow each modification. This repetitive cycle of protocol modifications rapidly followed by interactive performance reassessments against training cases appears to result in efficient and effective differential diagnostic skills improvements. A new generation of computer-based teaching and learning tools may have a significant impact on undergraduate clinical education.